Interplay of sociodemographic factors and dietary practices of elite Ethiopian athletes track in enhancing sports performance - Taye, Abdi G.; Singh, Ajita D. (International Journal of Scientific Reports, 2025)
Background: Dietary practices play a crucial role in athletic performance, particularly in endurance sports. In Ethiopia, known for its track athletes, the link between diet and performance is significant. This study explores the relationship between socio-demographic factors and dietary practices among Ethiopian track athletes to enhance performance. Methods: A descriptive survey method targeted ten public and private clubs, selecting 301 athletes from 1,220 randomly. Ten questionnaires assessed dietary practices (reliability: 0.792). Hypothesis testing at a 0.05 significance level used statistical package for the social sciences (SPSS) 26 with descriptive and inferential statistics. Descriptive analysis included frequency, percentages, mean, and standard deviation. An independent t-test compared dietary practices by gender, while one-way analysis of variance (ANOVA) analyzed variations by age, club, race, and experience. Results: The overall mean of 3.24 and standard deviation of 1.135 indicated moderate dietary adherence. The t-test showed a significant gender difference (t=3.514, p=0.047). ANOVA found no age-based difference (F=1.651, p=0.001) but revealed significant differences by club affiliation (F=2.301, p=0.016) and race (F=2.377, p=0.039). Experience showed no significant impact (F=0.190, p=0.001). Conclusions: The findings underscore the need for tailored nutrition education and support for athletes, emphasizing individualized approaches based on gender, club affiliation, and race. The study revealed suboptimal dietary practices among Ethiopian track athletes, highlighting the importance of comprehensive nutrition education interventions.